2015
DOI: 10.1186/s12866-015-0482-9
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte presence does not increase microbicidal activity of Platelet-rich Plasma in vitro

Abstract: BackgroundHuman platelets are a rich reservoir of molecules that promote regenerative processes and microbicidal activity. This activity might be increased by concentration in platelet-rich plasma (PRP) products and modulated by the presence of leukocytes. Despite extensive use in clinical procedures, only few studies have investigated PRP’s real microbicidal potential. Therefore, this study aimed at comparing the in vitro microbicidal activity of platelets and leukocyte-enriched PRP (L-PRP) to pure platelet-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 51 publications
0
37
0
5
Order By: Relevance
“…It is still a subject of debate whether leukocytes have a positive or negative effect on healing processes (15). They may have beneficial effects because they stimulate the immune response against infections (19), but it has been recently demonstrated that L-PRP and P-PRP generally inhibit bacterial growth in a comparable way (20); leukocytes also increase GF release, contributing to angiogenesis, matrix production and hypercellularity (21). On the other hand, leukocytes may release inflammatory cytokines (such as TNF-α and reactive oxygen species) that may increase inflammation, having a detrimental effect by delaying tissue healing (17,22).…”
Section: Discussionmentioning
confidence: 99%
“…It is still a subject of debate whether leukocytes have a positive or negative effect on healing processes (15). They may have beneficial effects because they stimulate the immune response against infections (19), but it has been recently demonstrated that L-PRP and P-PRP generally inhibit bacterial growth in a comparable way (20); leukocytes also increase GF release, contributing to angiogenesis, matrix production and hypercellularity (21). On the other hand, leukocytes may release inflammatory cytokines (such as TNF-α and reactive oxygen species) that may increase inflammation, having a detrimental effect by delaying tissue healing (17,22).…”
Section: Discussionmentioning
confidence: 99%
“…71 However, Mariani et al reported that leukocytes did not enhance the microbicidal activity of PRP in vitro, when L-PRP and pure PRP (P-PRP) were compared. 72 They concluded that the similar in vitro antibacterial activity of L-PRP and P-PRP may result from antimicrobial peptide release from both formulations, such as neutrophil-activating protein-2.…”
Section: Prp Antibacterial Propertiesmentioning
confidence: 99%
“…[10] Known facts and quality of evidence Despite the role of leucocytes in invalidating the bacterial growth, the fact that the myeloper-oxidate concentration was similar in products with and without leucocytes indicates the antibacterial role of platelets. [11] Nevertheless, bacterial growth inhibition is determined by the quality of PRP. Variables that influence the quality and quantity of PRP are: the number of donor's platelets, the type of activating and clotting agent, the number of centrifugation steps, the force of gravity, the validation of method with positive results from clinical trials.…”
Section: Introductionmentioning
confidence: 99%